Implementasi Evaluasi Kirkpatrick Level 2 dalam Program Pelatihan Administrasi Perkantoran Digital Berbasis Project Based Learning (Lembaga Pengembangan Kinerja Dosen, 2026)
The digitalization era has transformed the office administration landscape, demanding mastery of digital technology. However, evaluation of training programs at Vocational Training Centers still relies on simple indicators without structured instruments. This study aims to evaluate the implementation of Kirkpatrick Level 2 in measuring learning achievement of participants in the Google Workspace-based digital office administration training program using Project Based Learning methods at UPTD BLK Semarang City. The research employs a qualitative approach with a case study involving 16 training participants, 2 instructors, and 2 program managers through participatory observation, in-depth interviews, and documentation with data triangulation. The findings indicate that the implementation of competency unit-based evaluation according to SKKNI achieved an 80% pass rate with continuous monitoring during the 1-6 month post-training period. Five aspects of Kirkpatrick Level 2 demonstrated significant achievement, including an average knowledge improvement of 42 points with 75% of participants reaching minimum standards, a 78% skills success rate, 80% positive attitude change, 80% increase in digital confidence, and high enthusiasm (8-10/10). Internal factors affecting outcomes included heterogeneity in initial abilities with three adoption patterns (Enthusiastic adopters 35%, Gradual adapters 50%, Resistant learners 15%), diversity in learning styles, and strong internal motivation. External factors encompassed challenges such as unstable internet connections disrupting 40% of learning time, limited personal devices, and the complexity of learning paradigm shifts. Development recommendations include strengthening technological infrastructure, implementing personalized learning paths, adopting hybrid learning approaches, developing Industry 4.0-based curriculum, and establishing a structured peer coaching system to optimize the effectiveness of digital office administration training programs.